OPEN RESONATOR FOR SUMMATION OF POWERS IN SUB-TERAHERTZ AND TERAHERTZ FREQUENCIES - I. K. Kuz’michev; V. D. Yeryomka; A. V. Маy; A. S. Troshchilo (Radio Physics and Radio Astronomy, 2017)
Purpose: Study of excitation features for the first higher axialasymmetric type oscillations in an open resonator connected into the waveguide transmission line.